Формування комунікаційної політики в цифровому маркетингу з використанням маркетингових інструментів в економіці вражень - Татаринцева (Курбатова), Юлія Леонідівна (Український державний університет науки і технологій, 2025)
У статті досліджується трансформація комунікаційної політики підприємств в епоху економіки вражень. Мета дослідження полягає у розробці методичних рекомендацій з формування комунікаційної політики підприємства з використанням маркетингових інструментів в епоху економіки вражень. Актуальність роботи зумовлена втратою ефективності традиційних підходів до комунікацій у гіперконкурентному середовищі та необхідністю створення емоційно насичених вражень замість простого інформування про продукт. Обґрунтовано фундаментальні зміни при переході від трансакційно-орієнтованих комунікацій до побудови цілісних емоційних екосистем. Розроблено методичні рекомендації формування комунікаційної політики, особливість яких полягає в послідовній інтеграції аналітичних, стратегічних та операційних процесів для створення персоналізованих вражень на кожній точці дотику з брендом. The article examines the transformation of corporate communication policy in the experience economy era. The research objective is to develop methodological recommendations for forming enterprise communication policy using marketing tools in the experience economy. The object of research is the process of forming enterprise communication policy, while the subject comprises marketing tools for ensuring emotional consumer engagement. The relevance is determined by the loss of effectiveness of traditional communication approaches in hypercompetitive environment and the necessity to create emotionally rich experiences instead of mere product information dissemination. The study systematizes theoretical approaches to communication policy formation and identifies key marketing tools for creating consumer experiences. Theoretical foundations are analyzed, including the concept of experience economy where companies create value through memorable experiences, experiential marketing integrating five strategic experience modules, and contemporary marketing concepts emphasizing immersive technologies. Fundamental changes in communication policy formation process during transition to experience economy are substantiated. Classical communication policy focused on one-way mass messaging about product characteristics through rational arguments, while experience economy communication transforms it into two-way dialogue, shifts focus to emotional narratives, changes consumer role to active co-creator, expands channels to omnichannel ecosystems, and measures effectiveness through emotional engagement metrics rather than reach and conversion. An eight-stage methodology for communication policy formation is developed, the distinctive feature of which lies in sequential integration of analytical, strategic and operational processes for creating personalized experiences at each brand touchpoint. The methodology encompasses strategic audit with customer journey mapping, emotional positioning definition, omnichannel strategy development, multisensory content creation, coordinated implementation, engagement management through dialogue stimulation, performance monitoring via emotional analytics, and continuous optimization using predictive technologies. The practical value consists in providing enterprises with systematic approach to transforming traditional transactional communication into emotionally saturated interaction aimed at creating long-term loyalty and converting consumers into brand ambassadors in the experience economy context.
Forming communication policy in digital marketing using marketing tools in the impression economy
Keywords: комунікаційна політика; економіка вражень; маркетингові інструменти; емоційне залучення; омніканальна комунікація; цифровий маркетинг; communication policy; impression economy; marketing tools; emotional engagement; omnichannel communication; digital marketing